Development of Biocomposite Made from Reinforced Wheat Gluten with Oil Palm Fiber - Chaochanchaikul, Kantima; Krajangjeang, Atcha (Journal of Advanced Development in Engineering and Science, 2023)
This work aimed to develop wheat gluten (WG) based biocomposite by using oil palm fiber (OPF) as reinforcement for suitable single-use packaging applications. Because both WG and OPF are biodegradable materials. For specimen preparation, WG was melt-blended with OPF in an internal mixer and specimens were formed by using compression molding. The effects of OPF loading, varying from 0 to 15 wt%, were evaluated by tensile and impact testing, glass transition temperature (Tg) measurement, water absorption and morphological analysis. A 30 wt% of glycerol based on WG acts as a plasticizer. The increase in OPF loading resulted in the increases in tensile modulus, ultimate tensile stress, impact strength and Tg value whereas %elongation at break tended to decrease. The reinforcing effectiveness of OPF was attributed to the hydrogen bonding between the hydroxyl group of OPF and the peptide bond of WG. The water absorption of WG was interfered by the presence of OPF. WG based biocomposite containing OPF content of 15 wt% was the optimum formulation by consideration of changed properties.